EXAMINING THE COMMITMENT OF THE MANAGERS OF SMALL AND MEDIUM-SIZED ENTERPRISES IN CHINA TOWARDS CORPORATE STRATEGIC MANAGEMENT - Chen Kaiyue; Mohd Rahimie bin Abd Karim (Malaysian Journal of Business and Economics (MJBE), 2023)
In the current era, the trend of world economic integration has gradually strengthened, and international competition has become increasingly fierce. As an important factor in the development of enterprises, strategic management of enterprises is also valued and has a profound impact on the growth and development of enterprises. Therefore, it is of more important theoretical and practical significance to study the manager’s degree of emphasis on small and medium-sized enterprises to the strategic management of enterprises. Based on this, this study analyzes and explores the degree of commitment of small and medium-sized enterprises’ managers to corporate strategic management, focusing on the four influencing factors of corporate strategic management (business model, internal environment, external environment, and market competition) to conduct investigations and studies, and then analyze the manager’s degree of emphasis of small and medium-sized enterprises to the corporate strategic management. The main purpose of this study is to explore the managers’ degree of commitment toward strategic management. Through research and discussion, small and medium-sized enterprise managers will investigate and study the attitudes and behaviors of the four influencing factors of corporate strategic management to achieve the goal. This study uses quantitative research to test the hypotheses and collects data on behalf of independent variables and dependent variables through questionnaires. And this study used two commonly used software tools, SPSS and Smart PLS.